PARKINSON’S DISEASE - Titiek Sunaryati (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2011)
Parkinson's disease is a degenerative disorder of the central nervous system that often impairs thesufferer's motor skills, speech, and other functions. Parkinson's disease affects movement (motorsymptoms). Other typical symptoms include disorders of mood, behaviour, thinking, and sensation (nonmotorsymptoms). The symptoms of Parkinson's disease result from the greatly reduced activity of thedopaminergic neurons, which are primarily in the pars compacta region of the substantia nigra. Reviewsof depression estimate its occurrence in anywhere from 20-80% of cases. PD is not considered to be afatal disease by itself, but it progresses with time.